Pengaruh Keputusan Investasi, Keputusan Pendanaan dan Kebijakan Dividen Terhadap Nilai Perusahaan - Jesilia Jesilia; Sri Purwaningsih (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2020)
This study aims to examine the effect of investment decisions, funding decisions, dividend policies on firm value. This research was conducted on Consumer Goods Sector Companies listed on the Indonesia Stock Exchange (IDX). Samples were taken using a purposive sampling method. The total sample in this study was 72 samples. The method of data analysis uses multiple linear regression analysis. The results of this study indicate that investment decisions have a significant positive effect on firm value. While funding decisions and dividend policies do not affect the value of the company.